PENGEMBANGAN MEDIA PEMBELAJARAN TRANSLATION BALL TOURNAMENT (TBT) PADA MATERI TRANSFORMASI TRANSLASI BAGI SISWA SMA KELAS XI - YUNUS, MUHABAR; MAULIDIYA, DELLA; MAIZORA, SYAFDI (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2018)
The purpose of this research was to determine the level of validity, practicality, and effectiveness of Media Translation Ball Tournament (TBT) at Translation Transformation Lesson for High School Students Class XI. The type of this research was Development Research with adopting 4D procedure. This research was done by three stage. They were define, design, developthat consists of validity test, practicality test, and effectiviness test. Media Translation Ball Tournament (TBT) had average score validity, practical,and effectivenes ; 4,29, 4,32, and 4,34 with very valid categories, very practicalities categories and very effectively